Improving overnight loan identification in payments systems - Mark Rempel (Bank of Canada, 2014)
Information on the allocation and pricing of over-the-counter (OTC) markets is scarce. Furfine (1999) pioneered an algorithm that provides transaction-level data on the OTC interbank lending market. The veracity of the data identified, however, is not well established. Using permutation methods, I estimate an upper bound on the daily false positive rate of this algorithm to be slightly above 10%. I propose refinements that reduce the bound below 10% with negligible power loss. The results suggest that the inferred prices and quantities of overnight loans do provide viable estimates of interbank lending market activity. – – Il y a peu d'information au sujet de la répartition des actifs et de la formation des prix sur les marchés de gré à gré. En 1999, Furfine a conçu un nouvel algorithme qui fournit des données relativement aux transactions effectuées sur le marché du financement interbancaire. La validité de ces données n'est cependant pas bien établie. En procédant à une permutation des données, j'estime que la limite supérieure du taux de faux positifs quotidien généré par cet algorithme est légèrement au-dessus de 10 %. Je propose des améliorations permettant de réduire cette limite sous 10 % tout en subissant une perte de puissance statistique négligeable. Les résultats donnent à penser que les quantités et les prix des prêts à un jour déduits grâce à cette méthode constituent des estimations valables de l'activité sur le marché du financement interbancaire.
Keywords: E42; E44; C53; C38; G10; 330; Econometric and statistical methods; Financial markets; Interest rates; Payment clearing and settlement systems